Metabolomic Study of Three Species in Zingiberaceae Family based on 1H-NMR - Dinar Sari Cahyaningrum Wahyuni; Magdalena Kristanti; Soerya Dewi Marliyana; Yudi Rinanto (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Zingiberaceae is an economical plant and widely used as traditional medicines. Its rhizomes have been reported to have biological effects due to their metabolites content. However, metabolites profiling in Zingiberaceae has been little reported comprehensively. Therefore, this study aimed to profile primary and secondary metabolite of three species Zingiberaceae rhizomes (Zingiber amaricans BI, Zingiber officinale Roscoe, and Alpinia purpurata (Vieill.) K.Schum using 1H-NMR-based metabolomic approach. All samples were collected from local farmer located in Nguter, Sukoharjo, Central Java. Multivariate statistical analysis and ANOVA applied to measure the differences. It resulted that metabolite profiling discriminated between Zingiber and Alpinia samples. Fructose, α-glucose, β-glucose, sucrose, malic acid, alanine, valine, and shogaol contributed in discrimination between Z. amaricans BI, Z. officinale Roscoe, and A. purpurata (Vieill.) K.Schum. Sugar (α-glucose, β-glucose, fructose, and sucrose) and malic acid were significantly higher in Alpinia than in Zingiber samples. Relative concentration of amino acids (alanine and valine) and shogaol were significantly higher in Z. officinale. This result might be useful for databases and supplementary informations in Z. amaricans, Z. officinale, and A. purpurata taxonomy classifications.